A THz fiber polarization splitter based on anti-resonant hollow-core fiber with the asymmetric dual-suspended cores - Lu, Yipeng; Han, Zhongrui; Tian, Fengjun; Zeng, Zhibin; Chen, Youzhi; Xiu, Zhiguo; Liu, Sichen; liu, Chao; Yang, Xinghua; Zhang, Jianzhong (Frontiers in Physics, 2023)
In this paper a novel THz fiber polarization splitter based on anti-resonant hollow-core fiber with asymmetric dual-suspended cores has been proposed. For the proposed polarization splitter, the ultra-low confinement loss and great polarization splitting performance in the THz band can be achieved, which benefits from the good combination of anti-resonance mechanism with refractive index guidance mechanism. In order to confine the THz light wave well in the in the central large air hole, 8 sets of anti-resonance rings are introduced into the cladding of the fiber. Moreover, the asymmetric dual-suspended cores are used to control the polarization state of the guiding light for enhancing the polarization splitting effect, which exist in the central large air hole of anti-resonant hollow-core fiber. One of the dual cores is designed with a symmetrical structure to reduce the birefringence effect. The other core is designed with an asymmetric structure to increase that in the THz band. The numerical simulations results show that the THz polarization splitter with a length of 0.37cm is realized in the operating band around 1 THz by optimizing the geometric structure of the dual-suspended-core fiber, and the confinement losses of both x and y polarization modes are lower than 6×10-3dB/cm. Furthermore, the working bandwidth at the center frequency of 1 THz can reach 0.06THz, and the extinction ratio is better than 20 dB. The proposed THz polarization splitter has the characteristics of special short length, low loss and broad bandwidth. In conclusion, it has some potential applications of polarization devices in the field of optical fiber sensing and optical fiber communications.